El debate: estrategia didáctica para el fortalecimiento de los discursos orales - Morocho Paqui, Charly Manolo (2023)
The general objective of the research titled: The debate as a didactic strategy for improving oral speeches, determines how effective debate can be as a didactic strategy to strengthen students' oral speech abilities, as well as how effective debate can be as a didactic strategy to enhance students' oral speeches. The same was approached with three specific objectives. First, the goal was to determine whether debate could be used as a didactic strategy to strengthen oral speeches, second, to design an educational improvement proposal that used debate as a didactic strategy to improve oral communication, and third, to evaluate the applicability of an educational improvement proposal for strengthening oral communication. The descriptive research was conducted using a mixed approach and quasi-experimental design, inductive- deductive, analytical, synthetic, statistical methods, and for data collection techniques, such as observation, survey, and interview, were employed, which provided the necessary information for its analysis through instruments such as observation sheets and questionnaires. The population investigated was the school of Basic Education "Miguel Riofrío" in which through a non-probabilistic sampling 21 students, additionally, a teacher from the seventh grade was selected. The results acquired through the application of the educational proposal allowed demonstrating that the technique of debate as a didactic strategy favors significantly in the creation of innovative educational scenarios, resulting in a better development of communicative competences in the area of oral speech by the correct execution of pedagogical activities, which then improves learning outcomes in the area of Language and Literature. Key words: Debate, oral discourse, teaching, learning, education.